Benefit and Community Response to Surabaya Regional Drinking Water Company's Customer Complaints Service - Amelia Larasati Wandi; Amirul Mustofa (Universitas Medan Area, 2024)
Abstract This study aims to investigate the efficacy of RDWC customer complaint services in terms of their advantages and the response from the community in Surabaya City. This research employs a qualitative methodology with a descriptive approach to elucidate the problem of a particular phenomenon. The research data was collected by observing the customer complaint services of RDWC Surabaya City and conducting interviews with individuals who utilize these services. According to the research findings, application-based customer complaint services are now suboptimal and unsatisfactory for the community. That is evidenced by 1) multiple individuals expressing criticism of their experiences with RDWC services, specifically citing delayed response times from officers, and 2) people expressing dissatisfaction with the lack of response to their submitted complaints. This study provides a comprehensive analysis of the community's response to the services offered by RDWC Surabaya City. This research implies that the RDWC must promptly address all public complaints and is expected to enhance its services for better outcomes. Keywords: Utility Level, Community response, Government Services, Consumer Complaints.